Land use conversion to agriculture impacts biodiversity, erosion control, and key soil properties in an Andean watershed. Issue 3 (7th March 2022) - Galindo, Víctor; Giraldo, Carolina; Lavelle, Patrick; Armbrecht, Inge; Fonte, Steven J.
Abstract: The conversion of natural vegetation to agricultural land uses in mountainous Andean landscapes threatens an array of key ecological processes and ecosystem services (ES). In protected areas and buffer regions that provide water to cities, it is critical to understand how interactions between plants and soil communities sustain a range of ecosystem functions associated with nutrient recycling, soil structure, and erosion control. We sought to examine how land use conversion within a mountainous tropical forest landscape influences the diversity of vegetation and soil macrofauna communities, soil physicochemical properties, and hydrological regulation services. Biodiversity and a suite of key soil‐based ES were compared in five major land uses of the Cali River watershed: (1) annual cropping systems, (2) coffee plantations, (3) pastures, (4) abandoned shrubland, and (5) secondary forests. The diversity of woody and herbaceous vegetation, as well as soil macrofauna, was assessed in each land use. Soil chemical fertility and aggregate morphology were assessed via laboratory analyses and visual separation of soil aggregates based on their origin. Infiltration, runoff, and sediment production were measured using a portable rainfall simulator. We found a decrease in the diversity of woody vegetation across land uses to be associated with lower diversity of soil macrofauna. At the same time, agricultural management, annual crops in particular, supports the largest earthworm populations, likely due to increased organic inputs and low impact tillage, which appears not to diminish soil fertility and water infiltration. In contrast, the low soil fertility in pastures was associated with the lowest values of soil C, poor aggregation, and high bulk density and likely reflects overgrazing, with negative implications for water infiltration and erosion. Associations between the different sets of variables, evaluated with co‐inertia analysis, highlight the hierarchical relevance of plant cover and woody diversity on ES. The biological complexity associated with intact forest cover appears to generate "bundles" of co‐occurring ES, with this land use demonstrating the highest infiltration, and low runoff and sediment losses. Our findings demonstrate that forests and tree‐based agricultural systems may better contribute to the provision of multiple ES, including biodiversity conservation and hydrologic regulation.